Analisis Dampak Kebijakan Efisiensi Belanja Perjalanan Dinas Terhadap Kemandirian Fiskal Daerah Setelah Penerapan Undang-Undang Nomor 1 Tahun 2022 - Putriani V, Setiajeng (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
The efficiency of local government budget management has become a central issue in efforts to strengthen local fiscal autonomy, especially after the enactment of Law No. 1 of 2022 on Financial Relations between the Central Government and Local Governments. One of the strategic policies implemented is the efficiency of official travel expenses, which has been a significant expenditure item in the local budget. This study aims to analyze the impact of the efficiency policy for official travel expenses on regional fiscal autonomy, both in terms of changes in the APBD structure and the achievement of fiscal autonomy indicators before and after the implementation of Law No. 1 of 2022. The research method uses a quantitative approach with secondary data analysis of the APBD from several local governments, supported by qualitative studies through interviews with local finance officials. The results of the study indicate that the policy of efficiency in official travel expenses has a positive impact on increasing the proportion of productive spending and improving the fiscal autonomy ratio in most of the study areas. However, the impact of these policies varies across regions depending on their fiscal characteristics and financial management capacity. The implications of this research emphasize the importance of consistent budget reform and the strengthening of sustainable local fiscal governance to achieve more optimal fiscal autonomy.